The Effect of Technology in Information Searching Skills via Wiki to the Medical Students - Maryam Okhovati; Mina Moradzadeh; Farzaneh Zolala (Kerman University of Medical Sciences, 2014)
Background & Objective: Recently a new technology ie Web 20 has emerged and it is increasingly used in education Wiki is one of the web 20 application which is used in Elearning Wiki is a simple easy editable interactive application that enhances learning so this study was conducted to investigate the effect of using wiki on learning information searching skills on medical students in Kerman University of Medical Sciences Iran   Methods: The study population included the medical students who have chosen the information technology (IT) course in the second semester in 2013 The course was held in four groups two groups were selected randomly One group was considered as test group teaching through wiki (wikispaces) The second one was the control group traditional teaching (lecture) We asked about students attitudes toward learning through a researchermade questionnaire   Result: The most of the students (719%) have used at least one of the web 20 technologies and 219% used Wikis The mean scores of two groups increased and the difference between the mean scores was significant The mean and standard deviation of the students scores before and after training through Wiki enhanced from 280 ± 185 to 1285 ± 426 whereas it was 383 ± 430 to 1375 ± 325 in the traditional group (P < 0001) There was no significant association between two teaching methods (wiki and traditional) (P = 0560) and the improvement of both groups was almost equivalent but most of students (55%) preferred training by wiki   Conclusion: Teaching through Wiki had a positive effect on learning Regarding Wiki capabilities it can be used as a supplement method for teaching